2019
DOI: 10.1002/jbmr.3912
|View full text |Cite
|
Sign up to set email alerts
|

Back Pain-Inducing Test, a Novel and Sensitive Screening Test for Painful Osteoporotic Vertebral Fractures: A Prospective Clinical Study

Abstract: To detect painful vertebral fractures (VFs) in back pain populations at risk of osteoporosis, we designed a physical examination test (the Back Pain‐Inducing Test [BPIT]) that included three movements: lying supine, rolling over, and sitting up. If back pain is induced during any of these movements, the result is defined as positive, thereby establishing a presumptive diagnosis of painful VFs. Pain severity is quantified using a self‐reported numerical rating scale (NRS). The presence or absence of painful VFs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 49 publications
0
6
0
Order By: Relevance
“…The clinical pro les of the 358 patients enrolled in the study are shown in Table 1. The clinical pro les of OVFs are outlined as follows: (i) the most prevalent back pain site was localized in the thoracic-lumbar junction and lower (70.7%); unilateral back pain (49/358, 13.7%) and lumbosacral or buttock pain remote from the site of the lesion (14/358, 3.9%) was possible; (ii) the prevalence of the incident RP, SPT, and ASPP was 21.2%, 55.0%, and 23.2%, respectively; (iii) half of patients (51.1%) sought medical attention within two weeks of the onset of back pain, 16.5% of patients had delayed medical attention, and patients with a history of VF or VA did not seek medical aid at the rst point of the onset of back pain; (iv) 53.6% of patients had a spontaneous VF, and the precipitating events included falling from a standing height or less, coughing, sneezing, and routine everyday activity (lifting, bending, walking, and position changes); (v) the patient presented for care with a complaint, usually acute pain resulting in disability or di culty lying supine or sitting up from a supine position, such pain is elicited and refractory once the stress or loading on the axial spine changes and will subsides (even disappears) while the trunk is static; and (vi) the most frequent areas for VFs were the rst and second lumbar vertebrae (L1 and L2) and twelfth thoracic vertebra (T12) [12]. patients with radiating chest pain complained that the RP was more severe than the back pain.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…The clinical pro les of the 358 patients enrolled in the study are shown in Table 1. The clinical pro les of OVFs are outlined as follows: (i) the most prevalent back pain site was localized in the thoracic-lumbar junction and lower (70.7%); unilateral back pain (49/358, 13.7%) and lumbosacral or buttock pain remote from the site of the lesion (14/358, 3.9%) was possible; (ii) the prevalence of the incident RP, SPT, and ASPP was 21.2%, 55.0%, and 23.2%, respectively; (iii) half of patients (51.1%) sought medical attention within two weeks of the onset of back pain, 16.5% of patients had delayed medical attention, and patients with a history of VF or VA did not seek medical aid at the rst point of the onset of back pain; (iv) 53.6% of patients had a spontaneous VF, and the precipitating events included falling from a standing height or less, coughing, sneezing, and routine everyday activity (lifting, bending, walking, and position changes); (v) the patient presented for care with a complaint, usually acute pain resulting in disability or di culty lying supine or sitting up from a supine position, such pain is elicited and refractory once the stress or loading on the axial spine changes and will subsides (even disappears) while the trunk is static; and (vi) the most frequent areas for VFs were the rst and second lumbar vertebrae (L1 and L2) and twelfth thoracic vertebra (T12) [12]. patients with radiating chest pain complained that the RP was more severe than the back pain.…”
Section: Resultsmentioning
confidence: 99%
“…They were blinded to the clinical information and established the presence of a VF according to the following diagnostic criteria: low signal changes on T1-weighted images (T1WI) and high or low signal changes on T2-weighted images (T2WI), particularly high signal changes on short-tau inversion recovery (STIR) images [15][16][17]. The interrater consistency for interpreting MRI was perfect [12].…”
Section: Variables Assessment and Collectionmentioning
confidence: 99%
See 2 more Smart Citations
“…For this reason existing paininducing tests (e.g., hot plate test, tail flick test, etc.) solely use animals as experimental subjects or focus on the relation between a pre-existing pain condition with some specific movement (e.g., back pain-inducing test [2] examines the pain condition during movements of lying supine, rolling over, and sitting up). The challenge of designing a proper pain-inducing test leads to the second difficulty, which is that pain detection is thus limited in the medical field or clinical aspects.…”
Section: Introductionmentioning
confidence: 99%